Determinan Pemilihan Metode Operasi Wanita (MOW) di Puskesmas Lewoleba Kecamatan Nubatukan Kabupaten Lembata - Veronika Tuto Kalangona; Afrona E.L. Takaeb; Ribka Limbu; Petrus Romeo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Women’s Sterilization Method (MOW) is one of the most effective and efficient contraceptive methods to reduce birth rates or end pregnancies. This method offers optimal benefits with minimal side effects. Several factors may influence the choice of MOW contraception, including age, parity, education level, knowledge, attitude, husband’s support, healthcare workers’ support, and accessibility of services. This study aimed to determine the factors influencing the choice of MOW contraception among women of reproductive age at Lewoleba Public Health Center, Nubatukan District, Lembata Regency. This was a quantitative study with a cross-sectional design. Sampling was conducted using proportional random sampling, involving 66 respondents. Data were analyzed using the chi-square statistical test. The results showed a significant relationship between knowledge (p = 0.000), attitude (p = 0.000), husband’s support (p = 0.004), healthcare workers’ support (p = 0.000), and number of children (p = 0.000) and the selection of MOW. It is recommended that the Lewoleba Health Center continues to provide comprehensive and consistent education to enhance community understanding regarding long-term and permanent contraceptive methods.